Geographical Distribution of Global Radiation and Sunshine Duration over the Island of Cyprus - Pashiardis, Stelios; Pelengaris, Alexandros; Kalogirou, Soteris A. (My University, 2023)
In this work, hourly measurements of global solar irradiances obtained from pyranometers and sunshine duration data using either Kipp & Zonen CSD3 automatic sensors or Campbell–Stokes sunshine recorders were assessed through an extensive quality control procedure and statistical analysis on the measured and derived solar parameters for all the actinometric stations installed in various locations over the island of Cyprus, covering mainly the period 2019–2021. This information is useful for engineers concerning the solar energy capture systems and energy efficiency who can therefore take knowledge of the local radiation levels. Monthly mean hourly values of global radiation and sunshine duration are calculated and shown through isoline diagrams. During June or July, daily global irradiations ranged between 25 MJ/m2 and 30 MJ/m2, with the lowest occurring in the mountainous locations. On the other hand, in January or December, they ranged between 6.5 MJ/m2 and 10.5 MJ/m2. The total annual number of hours of sunshine duration ranged between 2500 and 3500, with the lowest values recorded at the mountainous sites. The clearness index and relative sunshine duration were used for the classification of the weather conditions over the island. Furthermore, the interrelationships between the said indices were used for the estimation of global radiation. This work has specifically contributed to the characterization and analysis of hourly and daily solar global radiation. Furthermore, the measurements on the ground level could be compared with satellite observations in order to improve the geographical distribution of global radiation, especially in areas where no measurements exist. The analysis could be also extended for the other shortwave radiation components (Direct, Diffuse and Photosynthetic Active Radiation (PAR)) in order to assess the solar radiation regime over the island.
Keywords: classification of sky conditions; clearness index; isoline diagrams; quality control; solar global radiation; statistical analysis; sunshine duration